Investigation of the Degradation of Chelate Complexes in Liquid Redox Desulfurization Processes - Holz, Stephan; Köster, Peter; Thielert, Holger; Guetta, Zion; Repke, Jens-Uwe (Chemical engineering & technology, 2020)
Metal complexes such as Fe‐EDTA, which are used as pseudo‐catalysts or oxygen carriers in wet oxidative desulfurization processes, are subject to a degradation mechanism that significantly influences the economics of such processes. Therefore, this study presents a methodology for determining the degree of degradation during the reactive hydrogen sulfide absorption in a Fe‐EDTA solution within a continuously operating semi‐batch reactor system. For this purpose, the reactive conversion of H2S in the liquid phase was used as a reference, and a clear dependence of the degradation on the pH could be shown. In addition, indicators are introduced that evaluate the observed pH dependency of the degradation and distinguish pH‐induced effects such as the pH‐dependent absorption performance of H2S. Wet oxidative desulfurization processes using metal complexes as catalysts are subject to catalyst decomposition. To enable efficient operation of these processes, the operating conditions must be selected so that the catalyst is presented in its most stable form. For this purpose, a methodology is presented to quantify the pH‐dependent degradation mechanism and distinguish it from other phenomena.